Antivenomics and in vivo preclinical efficacy of six Latin American antivenoms towards south-western Colombian Bothrops asper lineage venoms. - Diana Mora-Obando; Davinia Pla; Bruno Lomonte; Jimmy Alexander Guerrero-Vargas; Santiago Ayerbe; Juan J Calvete (Public Library of Science (PLoS), 2021)
Background Bothrops asper represents the clinically most important snake species in Central America and Northern South America, where it is responsible for an estimated 50-80% of snakebites. Compositional variability among the venom proteomes of B. asper lineages across its wide range mirrors clinical differences in their envenomings. Bothropic antivenoms generated in a number of Latin American countries commonly exhibit a certain degree of paraspecific effectiveness in the neutralization of congeneric venoms. Defining the phylogeographic boundaries of an antivenom's effectivity has implications for optimizing its clinical use. However, the molecular bases and impact of venom compositions on the immune recognition and neutralization of the toxic activities of across geographically disparate populations of B. asper lineages has not been comprehensively studied. Methodology/principal findings Third-generation antivenomics was applied to quantify the cross-immunorecognizing capacity against the individual components of venoms of three B. asper lineages (B. asper (sensu stricto), B. ayerbei and B. rhombeatus) distributed in south-western (SW) Colombia, of six Latin American antivenoms, produced against homologous (Colombia, INS-COL and PROBIOL) and Costa Rica (ICP)), and heterologous (Argentina (BIOL), Perú (INS-PERU) and Venezuela (UCV)) bothropic venoms. In vivo neutralization assays of the lethal, hemorrhagic, coagulant, defibrinogenating, myotoxic, edematogenic, indirect hemolytic, and proteolytic activities of the three SW Colombian B. asper lineage venoms were carried to compare the preclinical efficacy of three (Colombian INS-COL and PROBIOL, and Costa Rican ICP) antivenoms frequently used in Colombia. Antivenomics showed that all the six antivenom affinity matrices efficiently immunoretained most of the B. asper lineages venom proteins and exhibited impaired binding towards the venoms' peptidomes. The neutralization profile of the INS-COL, PROBIOL and ICP antivenoms towards the biological activities of the venoms of SW Colombian B. asper (sensu stricto), B. ayerbei and B. rhombeatus lineages was coherent with the antivenomics outcome. In addition, the combination of in vitro (antivenomics) and in vivo neutralization results allowed us to determine their toxin-specific and venom neutralizing antibody content. Noteworthy, heterologous INS-PERU, BIOL, and UCV bothropic antivenoms had equal or higher binding capacity towards the venoms components of SW Colombian B. asper lineages that the homologous Colombian and Costa Rican antivenoms. Conclusions/significance The combined in vitro and in vivo preclinical outcome showed that antivenoms manufactured in Colombia and Costa Rica effectively neutralize the major toxic activities of SW Colombian B. asper lineage venoms. The antivenomics profiles of the heterologous antivenoms manufactured in Argentina, Venezuela, and Perú strongly suggests their (pre)clinical adequacy for the treatment of B. asper lineage envenomings in SW Colombia. However, their recommendation in the clinical setting is pending on in vivo neutralization testing and clinical testing in humans. Bothrops asper is a highly adaptable snake species complex, which is considered the most dangerous snake throughout much of its distribution range from the Atlantic lowland of eastern México to northwestern Perú. Antivenoms are the only scientifically validated treatment of snakebite envenomings. Venom variation is particularly common in wide ranging species, such as B. asper, and may result in variable clinical presentations of envenomings, as is the case for the B. asper species complex, potentially undermining the efficacy of snakebite treatments depending on the immunization mixture used in the generation of the antivenom. Conversely, phylogenetic conservation of antigenic determinants confers an unpredictable degree of paraspecificity to homologous antivenoms produced for a geographic area, but also to heterologous congeneric antivenoms, towards the venom components of allopatric conspecific populations. This work aimed at comparing the preclinical profile of a panel of Latin American homologous and heterologous antivenoms against the venoms of B. asper lineages distributed in SW Colombia. The outcome of this study strongly suggests the suitability of considering the heterologous antivenoms BIOL (Argentina), UCV (Venezuela) and INS-PERU (Perú) as alternatives to homologous Colombian INS-COL and PROBIOL and Costa Rican ICP antivenoms for the treatment of envenomings by B. asper (sensu stricto) in W Colombia and Ecuador, B. ayerbei in Cauca and Nariño (Colombia), and B. rhombeatus in Cauca river valley, SW Colombia.